Spengelidae (Hemichordata: Enteropneusta) from the Eastern Pacific including a new species, Schizocardium californicum, from California - Cameron, C. B.; Perez, M. (Zootaxa, 2012)
Twenty one enteropneusts have been described from the west coast of North America, but those reports include no Spengelidae. Here we describe two species of acorn worms in the genus Schizocardium (S. californicum and S. peruvianum) on the basis of morphology. The former represent the first spengelid worm described from North American waters.  The latter is a previously described species, and here we expand on its morphological description and extend its geographic range north from Peru to California. Notes on the habit and localization of each species, as well as a dichotomous key to the genera of the family Spengelidae are provided.  Based on morphology, spengelids appears to represent an intermediate between the enteropneust families Harrimaniidae and Ptychoderidae, and Schizocardium is sister taxon to the ptychoderids. The disjunct and widely distributed populations of S. peruvianum and S. brasiliense, with populations in South American and North America, but none between, could represent the relict populations of formerly wide spread species, or the two extremes of ranges.